Mass spectrometry strategies to unveil modified aminophospholipids of biological interest. Issue 4 (30th December 2018) - Colombo, Simone; Domingues, Pedro; Domingues, M. Rosário
Abstract : The biological functions of modified aminophospholipids (APL) have become a topic of interest during the last two decades, and distinct roles have been found for these biomolecules in both physiological and pathological contexts. Modifications of APL include oxidation, glycation, and adduction to electrophilic aldehydes, altogether contributing to a high structural variability of modified APL. An outstanding technique used in this challenging field is mass spectrometry (MS). MS has been widely used to unveil modified APL of biological interest, mainly when associated with soft ionization methods (electrospray and matrix‐assisted laser desorption ionization) and coupled with separation techniques as liquid chromatography. This review summarizes the biological roles and the chemical mechanisms underlying APL modifications, and comprehensively reviews the current MS‐based knowledge that has been gathered until now for their analysis. The interpretation of the MS data obtained by in vitro ‐identification studies is explained in detail. The perspective of an analytical detection of modified APL in clinical samples is explored, highlighting the fundamental role of MS in unveiling APL modifications and their relevance in pathophysiology.